Effects of infection history on dengue virus infection and pathogenicity - Tsang, Tim K.; Ghebremariam, Samson L.; Gresh, Lionel; Gordon, Aubree; Halloran, M. Elizabeth; Katzelnick, Leah C.; Rojas, Diana Patricia; Kuan, Guillermina; Balmaseda, Angel; Sugimoto, Jonathan; Harris, Eva; Longini, Ira M.; et al. (Nature communications, 2019)
The understanding of immunological interactions among the four dengue virus (DENV) serotypes and their epidemiological implications is often hampered by the lack of individual-level infection history. Using a statistical framework that infers full infection history, we analyze a prospective pediatric cohort in Nicaragua to characterize how infection history modulates the risks of DENV infection and subsequent clinical disease. After controlling for age, one prior infection is associated with 54% lower, while two or more are associated with 91% higher, risk of a new infection, compared to DENV-naive children. Children >8 years old have 55% and 120% higher risks of infection and subsequent disease, respectively, than their younger peers. Among children with ≥1 prior infection, intermediate antibody titers increase, whereas high titers lower, the risk of subsequent infection, compared with undetectable titers. Such complex dependency needs to be considered in the design of dengue vaccines and vaccination strategies. Lack of knowledge of individual infection history hinders understanding of immunological interactions among DENV serotypes. Here, the authors introduce a framework to infer the relationship between unobserved infection history and subsequent infection and disease risk, and find complex dependencies.